PTH-021 A novel scissor and loop technique for endoscopic resection and closure of esd defects: resection of gastric submucosal tumour. (17th June 2017) - Kandiah, K; Subramaniam, S; Poller, D; Higginson, A; Bhandari, P
Abstract : Introduction: Endoscopic submucosal dissection (ESD) is a technique developed in Japan to enable curative en-bloc resection of early gastrointestinal neoplasia. This technique has been slow to be adopted in the West due to the lack of training, endoscopic knives requiring significant manual dexterity and a high rate of complications. Efforts have been made to improve training but until recently, there have been few advances improving endoscopic knife technology and the development of devices to reduce complications. We present a video demonstrating the utility of a novel scissor-type knife which can potentially make ESD accessible to Western endoscopists and the use of a novel large defect ligation device. Method: Various types of endoscopic knives (eg. insulated tip, hook, triangular, needle) have traditionally been used in ESD. The scissor-type knife was developed to facilitate the accurate grasping of tissue prior to dissection. The outer segment of the scissor arms are insulated and the inner segment of the arms have thin cutting blades for dissection. This knife is rotatable, thereby enabling dissection of difficult to access tissue. The novel large defect ligating loop device is a detachable plastic endoloop which can be dropped freely into the lumen. This is then caught and easily clipped along the edges of the defect. Finally the loop closure device can be reattached to the loop and ligate the defect. Results: A 72-year-old man was found to have a large SM tumour in the upper body (lesser curve) of his stomach. Assessment with enhanced endoscopic imaging showed normal gastric mucosa surface pattern. Endoscopic ultrasound showed that the lesion was of submucosa in origin. The case was discussed in the Upper GI MDT. A scissor-type knife enabled controlled mucosal incision and SM dissection even on retroflexion. Haemostasis was maintained using the scissor type knife, which is able to carry out the function of a haemostatic forceps, negating the need to change instruments during the procedure. The large resection defect was closed using a novel ligating device that is approximated like a purse string. There were no immediate or late complications. The patient was routinely discharged home the next morning. Conclusion: Novel scissor-type knives are technically easy to use even when the access is challenging. This type of knife can perform mucosal incision, SM dissection and maintain haemostasis effectively. A detachable large defect ligator can effectively close large ESD defects. Both novel devices have the potential to help facilitate the uptake of ESD in the West. Disclosure of Interest: K. Kandiah: None Declared, S Subramaniam: None Declared, D Poller: None Declared, A Higginson: None Declared, P Bhandari Conflict with: Receives educational grants from Fujifilm, Olympus and Pentax